KITAB SABILAL MUHTADIN KARYA SYAIKH MUHAMMAD ARSYAD ALBANJARI - Sri Ulfa Rahayu (SHAHIH (Jurnal Ilmu Kewahyuan), 2022)
There is one book that was famous in the 19th century, namely Sabilal Muhtadin, but now it is very difficult to find this book again because it is rarely studied. This book was written by 'Ulama Indonesia in Arabic Malay, namely Shaykh Muhammad Arsyad Al Banjari, a Banjari scholar who was born on 15 Safar 1122 H/19 March 1710 M and died on 6 Shawwal 1227 H coinciding with 13 October 1812 M. Purpose we write this article is to recognize and study this book again so that it is not lost. The method created is the method of literature with a historical approach, namely looking at history in relation to the author and the contents of the manuscript. The result is that this book consists of two volumes that fall into the category of Jurisprudence books with the Shafi'i mazhab which were famous in the 19th to 20th centuries. The full name of the book is Sabil al-Muhtadin Li at-Tafaqquh fi Amr ad-Din. This book was written because of the advice of the Sultan at that time, namely Sutan Tahmidullah who also liked to study religion. In 1882 M in Makkah at the expense and initiative of Shaykh Al-Fatani, a scholar from Pattani, this book was reproduced and printed. The second publication of the book Sabilal Muhtadin in Constantinople in 1302 H then the third time published in Egypt in 1307 H. World libraries that also store this book are Mecca, Beirut and Turkey. If you read the Book of Sabilal Muhtadin, it is rather difficult for the author to understand because the language style is not in accordance with the refined spelling. Because this book is an 18th century book, while the EYD only existed in the 19th century, namely in 1972.